Evaluating the impact of smallholder farming and its effectiveness in alleviating poverty in Sedibeng District Municipality of Gauteng Province, South Africa - Terblanche, S.J. (University of Pretoria, 2020)
Dissertation (MSc Agric (Agricultural Extension))--University of Pretoria, 2020.